1996
DOI: 10.1136/hrt.75.6.568
|View full text |Cite
|
Sign up to set email alerts
|

Prospective relations between Helicobacter pylori infection, coronary heart disease, and stroke in middle aged men.

Abstract: Objective-To determine whether Helicobacter pyloni, a chronic bacterial infection often acquired in childhood, is associated with increased risk of coronary heart disease and stroke later in life. Design-Nested case-control study. Setting-Prospective study of cardiovascular disease in men aged 40-59 years at entry (1978-1980) (Heart 1996;75:568-572) Keywords: coronary heart disease; Helicobacter pylori; stroke Factors acting early in life may influence adult risk of coronary heart disease,1 2 and play a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
85
0
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(93 citation statements)
references
References 27 publications
3
85
0
3
Order By: Relevance
“…[8][9][10][11]13 The OR of Coxsackie virus infection with HT was 3.17 after adjustment for age, male gender, drinking status, overweight, dyslipidemia, and log-CRP level. Coxsackie virus, a member of the enterovirus genus, is the most common cause of human myocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11]13 The OR of Coxsackie virus infection with HT was 3.17 after adjustment for age, male gender, drinking status, overweight, dyslipidemia, and log-CRP level. Coxsackie virus, a member of the enterovirus genus, is the most common cause of human myocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…Helicobacter pylori (H. pylori) is a microaerophilic spiral-shaped gram negative bacterium that chronically infects the stomach of more than 50% of the human population (varying from over 70% in developing countries to less than 40% in developed countries) and represents the major cause of gastroduodenal pathologies Science Publications AJI (e.g., chronic active gastritis, peptic ulcer, B-cell lymphoma and gastric carcinoma) (Wotherspoon et al, 1999;Parsonnet et al, 1991;D'Elios et al, 1997). Some recent epidemiologic and serologic studies have reported a relationship between H. pylori seropositivity, especially of the high virulent cytotoxin-asssociated gene A (CagA) positive strains and extra-gastroduodenal diseases, such as vascular (coronary artery disease and stroke), metabolic (autoimmune atrophic thyroiditis), rheumatic (Henoch-Schönlein purpura), dermatologic (chronic urticaria and rosacea), as well as respiratory diseases (chronic bronchitis, COPD, bronchiectasis, asthma and lung cancer) (Whincup et al, 1996;Luis et al, 1998;Tsang et al, 1998;Roussos et al, 2006;Jun et al, 2006;Behroozian and Moradkhan, 2010). The activation of inflammatory mediators as a result of systemic immune response induced by H. pylori infection may be potential explanation for these associations (Kanbay et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Some reports have shown a positive relation between HP infection and coronary heart disease [6][7][8] , while others have found no such relationship 2,[9][10][11] . In regards to the relation between HP infection and stroke, positive 12) and negative 13) test results have been reported. It has also been reported that the eradication of HP and antibiotics against HP reduced the recurrence rate of acute coronary events 14,15) .…”
mentioning
confidence: 99%